Problems of Administering a Value-Added Tax in Developing Countries - Casanegra de Jantscher, Milka (Washington, D.C. : International Monetary Fund, 1986)
During the 1970s and 1980s, many developing countries enacted value-added taxes (VATs) as a part of their fiscal structures. The productivity of this source of revenue has depended in large part on the facility with which the tax can be administered. Single rate VATs have proved easier to administer than those with multiple rates. Exemptions and zero-rating tend to complicate administration. Because small taxpayers are so numerous in developing countries and administrative resources so limited, the treatment of small taxpayers has required special attention. The difficulty of taxing services has led most developing countries to omit all but a few services from the tax base. Administrative constraints are the main reason why the VAT that prevails in developing countries is usually very different from the broad-based and neutral tax discussed in public finance treatises.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet